Battery structure

By using fiber composite components of long fibers and unsaturated compound matrix materials as protective devices, the problem of overly strong design when protecting batteries in the prior art is solved, and better flame and mechanical protection effects are achieved while maintaining good processing performance.

CN119731842APending Publication Date: 2025-03-28SGL CARBON SE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380060215.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-17
Filing Date
2023-07-05
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art design is too strong when protecting batteries from flame erosion and mechanical loads, resulting in reduced process performance, increased component weight and increased installation space.

Method used

A fiber composite material component containing fiber material containing long fibers and/or continuous fibers and an unsaturated compound matrix material is used as a protective device. The fiber material is embedded in the matrix material, and the matrix material contains unsaturated polymer to improve flame retardancy and mechanical properties.

Benefits of technology

Improved protection effects in flame erosion and mechanical loads are achieved without accompanied by reduced machining performance, increased component weight or increased installation space.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731842A_ABST
    Figure CN119731842A_ABST
Patent Text Reader

Abstract

The invention relates to a battery structure comprising a protective device, a protective device for a battery housing and a fiber-matrix semi-finished product for producing the protective device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a battery structure comprising a battery housing and / or a battery and a protective device, a protective device for the battery housing and / or the battery, and a fiber-matrix semi-finished product for producing the protective device. Background Art

[0002] In the course of the increasing demands on modern energy storage concepts, especially in the field of electromobility, increasingly larger energy storage units are being installed, in particular battery modules and cells with the highest possible energy density. If the chemicals and energy contained in the battery are released in an uncontrolled manner, this can lead to catastrophic fires. Among other things, such processes can also be triggered by mechanical damage to the battery. Since fiber composites offer advantages over metals in terms of the combined requirements of fire protection, crash safety, insulation and lightweight construction, battery boxes made of this material are increasingly being used. Due to their typical layer-based structure and the process-related simultaneous production of the material and the component composed thereof, fiber composites offer better possibilities for adapting to the specific requirements of the component compared to metals.

[0003] Fiber composite material components are known from the prior art which can better meet the above-mentioned requirements, in particular by realizing different functions such as flame retardant effects or electromagnetic shielding.

[0004] For example, US2005 / 0170238 A1 discloses a battery housing formed of a flame retardant polymer composition made of high-density polyethylene, which may include glass fiber reinforcement and a fire-resistant additive. During the production process, the fire-resistant additive is mixed with the polyethylene to be protected in the melt, and the mixture is then pressed into the desired shape. US2020 / 0152926 A1 describes a cover for an electric vehicle battery pack having a frame composed of a layer composite material. The first layer of the composite material includes a so-called "shear panel (Schertafel)", which has a fiber-reinforced composite layer intended to offset shear deformation during impact. As a separate element, the layer composite material includes a fire-resistant and wear-resistant second functional layer, which is deposited on the shear panel, and when the shear panel is connected to the frame of the vehicle, the second functional layer faces the battery.

[0005] Although the use of the above-mentioned fiber composite components allows for better protection of the components from external influences such as fire or mechanical loads, in many applications, especially in the field of battery technology, this protection is insufficient and / or requires the protection devices (e.g. shear panels) to be designed so robustly that the use of composite materials is no longer competitive. Alternatively, large amounts of flame-retardant or fire-extinguishing additives (e.g. phosphates or aluminum hydroxide) can be added to the composite components to increase the fire protection. However, these adjustments lead to performance losses both on the process side (increased scrap rates) and on the product side (increased weight).

[0006] Purpose

[0007] Against this background, the object of the present invention is to provide a battery structure with a protective device, by which the above-mentioned disadvantages can be overcome and which has an improved protection effect with regard to flame erosion and / or mechanical loads (flammabrasive-und / odermechanische Belastungen) without being accompanied by a reduction in processing performance and / or an increase in component weight and / or an increase in installation space. Summary of the invention

[0008] According to the invention, this object is achieved by a battery structure, which comprises a battery housing and / or a battery and a protective device, wherein the protective device is preferably arranged on one of the inner sides of the battery housing and / or on the battery, wherein the protective device has:

[0009] a) fibrous materials comprising long fibers and / or continuous fibers; and

[0010] b) Matrix material,

[0011] Therein, the fiber material is at least partially, preferably completely, embedded in a matrix material, wherein the matrix material contains unsaturated compounds, preferably unsaturated polymers, or consists of these materials.

[0012] The present invention relates to a battery structure preferably for an electric vehicle, comprising a protective device and a battery. As an alternative or in addition to the battery, the battery structure comprises a housing for the battery. In the first case ("alternatively"), the battery structure does not necessarily have to include a battery, i.e. the present invention already relates to a structure comprising only a battery housing with an additional protective device (and optionally a battery). In other words, the protective device is an additional independent element of the battery housing, which can optionally include a battery.

[0013] However, according to the invention, the protection device can also form a battery housing or a part of a battery housing, preferably a base plate or a cover plate of the battery, ie the protection device is the battery housing (or a part thereof). In this case, the battery structure necessarily includes the battery.

[0014] Battery modules are often used in modern battery construction. These battery modules are devices with multiple batteries, which are combined in a usually closed frame and connected to the outside via a uniform boundary. Usually, a plurality of such structurally dependent battery modules are arranged in a battery housing. The protection device according to the invention can be suitable for protecting a single module, i.e. it can be arranged between the battery housing and the battery module. However, the protection device according to the invention can also protect multiple modules, or even all modules.

[0015] Since the protection device according to the invention provides protection in particular against thermal and / or flame loads, it is preferably arranged between the battery housing and the battery module.

[0016] The protective device according to the invention can also be a so-called "intercell barrier" of a battery module, i.e. a protective plate which separates the individual cells of a battery module from one another. In the event of a fire, such a plate can prevent the flame of one cell from spreading to the adjacent cell(s). Particularly preferably, the protective device according to the invention is an "intercell barrier" between the pouch cells of a battery module.

[0017] In a preferred embodiment, the protection device according to the present invention is arranged on the inner side of the battery housing, preferably between the battery and the battery housing. In another embodiment of the present invention, the protection device according to the present invention is arranged on the outer side of the battery housing.

[0018] The protective device according to the present invention is a fiber composite material component, which includes a fiber material and a matrix material, the fiber material contains long fibers and / or continuous fibers, or is composed of long fibers and / or continuous fibers, and the matrix material has unsaturated compounds, especially unsaturated polymer materials. Unsaturated compounds refer to organic compounds whose molecular structure contains one or more carbon-carbon double bonds or triple bonds. However, in the context of the present invention, the term also includes molecular structures with carbon-nitrogen double bonds or carbon-nitrogen triple bonds. Particularly preferred are polymers with one or more carbon-carbon double bonds or triple bonds. In this article, "polymer" is understood to be a chemical substance containing more than 50wt%, preferably more than 70wt%, more preferably more than 80wt%, even more preferably more than 90wt%, and most preferably more than 95wt% of macromolecules.

[0019] A "macromolecule" is a molecule consisting of one or more identical or similar structural units (i.e., structural repeating units) (IUPAC Chemical Terminology, 2nd edition ("Golden Book"), AD McNaught, A. Wilkinson, Blackwell Scientific Publishers, Oxford (1997), SJ Chalk, ISBN 0-9678550-9-8). Such a macromolecule has more than 10 repeating units, preferably more than 15 repeating units. Its molar mass is preferably at least 3,000 g / mol, preferably at least 5,000 g / mol, particularly preferably at least 7,000 g / mol, and most preferably at least 10,000 g / mol.

[0020] Polymers are usually prepared by reacting monomers or oligomers containing one or more structural repeating units in a polymerization reaction. Here, oligomers are molecules formed from a plurality of monomers and thus composed of a large number of structurally identical or similar structural units. In the context of the present invention, oligomers are molecules resulting from the reaction of 2 to 10, preferably 2 to 8, preferably 3 to 7 monomers.

[0021] According to the invention, "resins" are understood to be precursors of thermosetting plastics, i.e. polymers (see IUPAC Chemical Terminology, 2nd edition ("Golden Book"), AD McNaught and A. Wilkinson, Blackwell Scientific Publishers, Oxford (1997)), which are particularly useful as components of coatings, varnishes and paints. Particular preference is given to resins which are obtained, in particular, by polyaddition or polycondensation reactions, in particular polyurethane (PU) resins, polyester resins, polyamide resins, urea-formaldehyde resins, melamine resins, formaldehyde resins, PVC resins, acrylic resins or epoxy resins.

[0022] A "fiber composite component" is understood to be a material which is a combination of two or more materials, which has material properties that differ from those of its individual components and which can be used as a component of a technical component (technischen Gegenstand). For example, such a component can be a plate or a shell, or a part of a shell, such as a base plate or a cover plate. However, the term "fiber composite component" also includes fiber composite components which can themselves form a technical component. A fiber composite component comprises at least one fiber material and a matrix material. The fiber composite component according to the invention is preferably a glass fiber reinforced plastic (GRP) or a carbon fiber reinforced plastic (CFRP).

[0023] The protective device according to the invention, i.e. the fiber composite component according to the invention, is suitable for protecting a battery and / or a battery housing and / or for protecting the battery, more precisely for preventing dangers caused by the battery. The protective device is particularly suitable for protecting the battery and / or the battery housing from mechanical loads and / or for preventing thermal and / or fire loads caused by the battery, for example in the event of a fire due to overheating or an uncontrolled chemical reaction of the battery chemistry. That is, the protective device protects the battery and / or the battery housing from pressure loads and / or tensile loads and / or shear loads and / or impact loads, which are usually introduced from the outside and could damage the battery, and on the other hand, in the event of a battery fire, prevents or at least reduces thermal and / or fire loads on the components surrounding the battery (e.g. the battery housing, if present).

[0024] Long fibers are fibers with a length of L=1 to 50 mm, while continuous fibers (also called unidirectional fibers) are fibers with a length of L>50 mm. Preferably, the fiber length of the fiber material is >30 mm. In the protective device according to the invention and / or in the fiber-matrix semi-finished product according to the invention, continuous fibers are preferably used. As a result, the component has particularly advantageous mechanical properties.

[0025] The matrix material of the protective device according to the invention serves to at least partially, preferably completely embed the fiber material and optionally also to at least partially, preferably completely embed the optional additive and / or to at least partially, preferably completely dissolve the optional additive. The matrix material holds the fibers of the fiber material in their position and transmits and distributes stresses between the fibers. The matrix material is preferably a polymer material, in particular a thermosetting polymer material. Preferably, the matrix material is a thermosetting polymer material made of a resin and a curing agent. In the production process, preferably accelerators, activators and release agents are used, which are preferably part of the matrix material in the sense of the present invention.

[0026] Preferably, apart from optionally added additives and added fiber materials, the matrix material has a substantially homogeneous chemical composition, ie apart from optionally added additives and added fiber materials, material boundaries do not exist at all or exist only in adjacent regions of the fiber composite material component.

[0027] The spatial dimensions of the protective device itself are not limited by the scope of the invention. Preferably, the protective device can be a board, such as a fireproof board. Preferably, the protective device is of monolithic design or a fiber composite sandwich panel, i.e. a plate-like component made in a sandwich construction. In the case of a sandwich construction, materials with different properties are combined in layers to form a component or semi-finished product. Typically, a sandwich panel comprises absorbent, strong outer covering layers, which are kept at a certain distance from a relatively soft, lightweight core material. The core material is preferably made of solid material (e.g. polyethylene, balsa wood), foam material (e.g. rigid foam, metal foam), insulating material (e.g. rigid foam, mineral wool) or honeycomb grid (e.g. paper, cardboard, metal, plastic). The core material transmits the shear forces that occur and supports the outer covering layers. In a fiber composite sandwich panel, at least one layer (usually one of the covering layers) is made of fiber composite material. Preferably, all outer covering layers are made of fiber composite material. Preferably, at least one, preferably all covering layers have a corrugated structure. The protective device preferably includes surface films, treatment films, protective films (especially UV protective films), marking films and color films, as well as films for improving electromagnetic compatibility (EMC). Also particularly preferred are covering functional layers, such as protective films for transportation and in-mold coatings, such as for improving paintability.

[0028] The protection device may also comprise pores, ie air and / or gas inclusions, but the volume of these pores preferably does not exceed 5 vol% of the total volume of the protection device.

[0029] The protective device is usually exposed to high mechanical loads in its intended application and therefore preferably has a particularly high mechanical resistance and / or strength.

[0030] Therefore, in a preferred embodiment of the present invention, the fiber composite material component (i.e., the protective device) has a flexural strength determined according to DIN EN ISO 14125:2011-05, which is ≥100 MPa, preferably ≥200 MPa, more preferably ≥400 MPa, still more preferably ≥600 MPa, even more preferably ≥750 MPa, and most preferably ≥1,000 MPa, but generally does not exceed 20,000 MPa.

[0031] In a preferred embodiment of the present invention, the fiber composite material component has a flexural modulus of elasticity determined according to DIN EN ISO 14125:2011-05, which is ≥10 GPa, preferably ≥20 GPa, more preferably ≥30 GPa, still more preferably ≥50 GPa, even more preferably ≥70 GPa, and most preferably ≥100 GPa, but generally does not exceed 1,000 GPa.

[0032] The protective device does not necessarily have to have the above-mentioned mechanical properties. For example, the protective device can also be used in combination with a second protective device made of a metal material, and the second protective device is mainly used for mechanical protection of the battery and / or the battery housing. Therefore, in a preferred embodiment of the present invention, the battery structure includes a second protective device made of a metal material.

[0033] Preferably, the battery structure according to the invention can be a stationary battery structure, but in another embodiment it can also be a battery structure for a means of transport, such as a motor vehicle or an aircraft. In the sense of the invention, the term "battery" is not limited to primary cells (i.e., batteries that cannot be recharged), but also includes (and even particularly preferably includes) accumulators, which are also referred to as secondary cells, i.e., rechargeable batteries. In this context, the battery is particularly preferably a lithium-ion accumulator, in particular a lithium-ion accumulator for an electric vehicle.

[0034] Conventional carbon-based protective devices without unsaturated carbon-carbon or carbon-nitrogen bonds in the matrix act as sacrificial materials, i.e., during thermal runaway, e.g. when the battery explodes due to overheating, the fully saturated matrix material is essentially completely oxidized to gaseous products such as CO2 and thus decomposes. An example of this is filled epoxy composites. On the other hand, other non-carbon-based matrix materials (e.g., silicones) can be used as insulators, but they have non-temperature-stable binders that fail prematurely under thermal and mechanical loads.

[0035] The inventors found that flame retardancy can be significantly improved by using a matrix material containing unsaturated carbon compounds. Not bound by this theory, the inventors assume that the unsaturated carbon bonds in the matrix material act as carbonization centers in the case of thermal runaway, that is, cyclization processes, dehydrogenation processes and aromatization processes occur in this case, thereby producing (partially) aromatic carbonaceous structures. These strongly endothermic processes cause the energy transferred to the protective device due to thermal runaway to be absorbed and dissipated. The carbonized layer acting as an insulator can also shield the heat of the matrix material on the other side of the carbonized layer. Electrical insulation can be further achieved by the non-carbonized area of ​​the matrix material. The long fiber or continuous fiber structure stabilizes the carbon structure formed during thermal runaway, and can absorb the mechanical load generated when the battery explodes, and allows the protective device to be only slightly deformed. In other words, the synergistic effect of the fiber material and the matrix material makes carbonization possible without damaging the slightly brittle structure formed by cracks or similar defects. In most cases, the composite structure can be prevented from being burned through. In addition, long fibers and / or continuous fibers are able to improve the performance of the protective device with respect to mechanically transferable loads (tensile, compressive, shearing forces) and to increase the flame retardant effect. Compared with short fibers, inhomogeneities in the component (e.g. local fiber volume content fluctuations) occur only to a lesser extent and, in addition, unstable structures such as exposed short fibers can be avoided during combustion.

[0036] These functions can be achieved in a locally focused manner by using unsaturated compounds in a locally limited manner. For example, unsaturated, preferably thermosetting polymer materials can be arranged only in selected areas of the matrix material, especially when only certain areas of the protective device are arranged in the immediate vicinity of the battery, battery housing or battery module.

[0037] The matrix material according to the invention can also be a multi-component matrix material, in particular a matrix material formed by a mixture of different polymer materials, wherein at least one of these polymer materials is an unsaturated polymer material. The unsaturated polymer material is then preferably arranged in an area adjacent to the battery, battery housing or battery module. In this multi-material matrix method, for example, during production, a phenolic resin (e.g., a linear phenolic resin (Novolak)) can first be applied to the mold and cured at a local critical position, which is in direct contact with the battery in subsequent use, for example. In a subsequent step, a second saturated resin system (e.g., an epoxy resin) is applied to the cured structure and the component is cured.

[0038] In a preferred embodiment of the present invention, the matrix material is a matrix material that is cured by adding a curing agent.

[0039] In a preferred embodiment of the present invention, the weight ratio of the unsaturated compounds, preferably polymeric and thermosetting compounds in the matrix material is ≥10wt%, preferably ≥20wt%, more preferably ≥40wt%, even more preferably ≥60wt%, further preferably ≥80wt%, and most preferably ≥90wt%. In a particularly preferred embodiment, the matrix material consists of unsaturated compounds, which are preferably in the form of thermosetting polymer materials.

[0040] In a preferred embodiment, the volume ratio of matrix material to fiber material in the protective device (ie the fiber composite material component) is 8:1 to 1:10, preferably 5:1 to 1:8, particularly preferably 2:1 to 1:5.

[0041] In a preferred embodiment, the weight ratio of matrix material to fiber material in the fiber composite material component is 5:1 to 1:20, preferably 3:1 to 1:10, particularly preferably 1:1 to 1:8.

[0042] In a preferred embodiment, the volume ratio of matrix material to optional additives in the fiber composite component is 100:1 to 1:5, preferably 50:1 to 1:3, particularly preferably 2:1 to 1:2.

[0043] In a preferred embodiment, the weight ratio of matrix material to optional additives in the fiber composite component is 100:1 to 1:10, preferably 50:1 to 1:6, particularly preferably 4:1 to 1:4.

[0044] In a preferred embodiment, the weight proportion of the fiber material in the total mass of the fiber composite component is 10 to 95 wt%, preferably 20 to 90 wt%, more preferably 30 to 85 wt%, even more preferably 40 to 80 wt%, most preferably 50 to 75 wt%.

[0045] In a preferred embodiment, the volume ratio of the matrix material to the fiber material in the functional region is 8:1 to 1:15, preferably 2:1 to 1:10, and particularly preferably 1:1 to 1:10. By adjusting the fiber volume content within the above range, the carbonization performance can be further improved.

[0046] In a preferred embodiment, the weight ratio of the matrix material to the fiber material in the functional region is 5:1 to 1:30, preferably 2:1 to 1:20, and particularly preferably 1:1 to 1:15.

[0047] Preferably, in the protective device, the fiber volume content is in the range of 30-70 vol%, preferably in the range of 35-65 vol%, more preferably in the range of 40-60 vol%, and most preferably in the range of 45-55 vol%. Thus, suitable mechanical properties for protection are achieved, in particular suitable ductility is achieved.

[0048] In a preferred embodiment of the invention, the fiber material at least partially, preferably completely, has a surface structure, preferably a textile surface structure, and is partially, mostly (ie more than 90 vol%) or even completely embedded in a matrix material.

[0049] Particularly preferably, the surface structure is selected from the group consisting of a laid scrim, a knitted fabric, a woven fabric, a braided fabric, a nonwoven fabric or a mixture thereof.

[0050] According to the invention, a nonwoven is understood to be a structure consisting of fibers of limited length, continuous fibers (filaments) or cut yarns of any type and origin, which are linked in some way to form a fiber layer and are connected to each other in some way. This does not include the crossing or interweaving of the yarns, such as occurs in the production of weaving, weaving, hand knitting, lace making, braiding and tufting products. This definition corresponds to the standard DIN EN ISO 9092. According to the invention, the term "nonwoven" also includes felt materials. However, films and papers are not regarded as nonwovens.

[0051] In the sense of the present invention, weaving is understood to be the regular interlacing of multiple threads made of a flexible material. The difference from weaving is that during weaving, the threads are not fed at right angles to the main production direction.

[0052] Particularly preferred within the scope of the present invention is the use of fiber materials in the form of woven fabrics. According to the present invention, a woven fabric is understood to be a fabric surface structure consisting of two thread systems, namely warp threads (warp) and weft threads (weft) which intersect in a pattern at an angle of exactly or approximately 90° when viewed from the fabric surface. Each of the two systems can be composed of a variety of warp or weft yarn types (e.g., basic warp threads, pile warp threads and padding warp threads; basic weft threads, binding weft threads and padding weft threads). The warp threads extend in the longitudinal direction of the woven fabric and are parallel to the selvedge, while the weft threads extend in the transverse direction and are parallel to the fabric edge. The threads are connected to the woven fabric primarily by friction engagement. In order for the woven fabric to be sufficiently non-slip, the warp threads and weft threads must generally be woven relatively tightly. Therefore, with a few exceptions, the woven fabric also has the appearance of a closed fabric. This definition corresponds to Part 1 of the standard DIN 61100.

[0053] According to the invention, the terms "woven fabric" and "nonwoven fabric" also include tufted textile materials. Tufting is a process in which yarns are anchored in a woven or nonwoven fabric using a machine driven by compressed air and / or electricity.

[0054] According to the invention, knitted fabric is understood to be a textile material produced from a thread system by knitting. This includes crocheted materials and knitted materials.

[0055] According to the invention, a laying scrim is understood to be a fabric consisting of one or more layers of parallel extending stretch threads. The threads are usually fixed at the intersections. The fixing is achieved by material bonding or mechanically by friction and / or shape locking. Preferably, the laying scrim is selected from uniaxial or unidirectional scrims, biaxial or multiaxial scrims.

[0056] Preferably, the fiber material has an anisotropic structure, ie in the functional layer according to the invention, the fibers have a specific fiber direction. Thus, anisotropic mechanical properties of the layered composite material can be produced.

[0057] Preferably, the fibers of the fiber material are selected from the group consisting of glass fibers, carbon fibers, ceramic fibers, basalt fibers, boron fibers, steel fibers, polymer fibers (e.g. synthetic fibers, in particular aramid and nylon fibers) or mixtures of the aforementioned fibers. Glass fibers and carbon fibers are particularly preferred. With suitable fibers, a protective device according to the invention having a particularly high mechanical resistance can be produced.

[0058] Carbon fibers are particularly preferably used for protective devices in aircraft applications, particularly due to their weight advantages and higher modulus of elasticity, while glass fibers are particularly preferably used in automotive applications.

[0059] In a further preferred embodiment, the fibers of the fibrous material are natural fibers, in particular natural polymer fibers.

[0060] Natural fibers are understood to be fibers which come from natural sources such as plants, animals or minerals and which can be used directly without further chemical conversion reactions. Examples thereof according to the invention are flax, jute, sisal or hemp fibers, as well as protein fibers or cotton. According to the invention, regenerated fibers can also be used, i.e. fibers which have been produced by chemical methods from naturally occurring, renewable raw materials.

[0061] The corresponding fiber materials are characterized by improved recyclability and are therefore particularly sustainable.

[0062] During thermal runaway, one or more unsaturated carbon-carbon and / or carbon-nitrogen bonds of the unsaturated compound are converted into (partially) aromatic carbonaceous structures. The inventors assume that the use of unsaturated carbon-nitrogen bonds leads to the elimination of N2 as part of the carbonization process. Therefore, in a preferred embodiment of the present invention, the functional group comprises a carbon-nitrogen bond, in particular a carbon-nitrogen double bond.

[0063] In another preferred embodiment of the present invention, the functional group comprises an unsaturated carbon-carbon bond, in particular a carbon-carbon double bond.

[0064] More preferably, the functional group contains two, three, four, five or more unsaturated carbon-carbon bonds and / or unsaturated carbon-nitrogen bonds.

[0065] In a preferred embodiment of the present invention, the unsaturated compound is a thermosetting polymer material having at least one structural repeating unit having at least one functional group containing an unsaturated carbon-carbon bond and / or an unsaturated carbon-nitrogen bond.

[0066] In a preferred embodiment, the functional group comprises two or more bonds selected from the group consisting of unsaturated carbon-carbon bonds and unsaturated carbon-nitrogen bonds, wherein at least two of these bonds are conjugated. The conjugation of the unsaturated bonds contributes to the formation of an aromatic structure, thereby facilitating the carbonization process and thus proceeding to a higher degree.

[0067] Preferably, functional group is a part for aromatic system, for example is a part for furyl, thienyl, pyrrole radicals, imidazolyl, pyrazolyl, oxazolyl, thiazolyl, phenyl, benzoyl, hydroxyphenyl or pyridyl. Due to the existence of aromatic system, energetically help the further aromatization in the carbonation process. When unsaturated compounds was a polymkeric substance, above-mentioned group was preferably a part for (multiple) repeating units particularly.

[0068] Preferably, the unsaturated compound is a thermosetting polymer selected from the group consisting of phenolic resins, cured melamine resins, cured furan resins and cured polyurethane resins. Particularly preferred are materials obtained by curing phenolic resins, preferably novolac resins. The thermosetting polymer material is preferably almost completely crosslinked, where "almost completely" means that at least 80% of the potentially crosslinkable functional groups are crosslinked.

[0069] Preferably, the thermosetting polymer material is a phenolic resin obtained by crosslinking a phenol-formaldehyde resin. The molar ratio of formaldehyde to phenol in the curable phenolic resin is particularly preferably in the range of 1:0.4 to 1:2.5, in particular between 1:1.2 and 1:2.

[0070] The thermosetting polymer material according to the present invention is preferably obtained by reacting a resin (e.g., a phenolic resin) with a curing agent. The curing agent is preferably selected from the group consisting of a formaldehyde donor (e.g., hexamethylenetetramine) or a melamine or urea condensate containing hydroxymethyl groups. Preferably, the amount of the curing agent is 2.5 to 50 wt%, preferably 5 to 15 wt%, based on the phenolic resin.

[0071] In a preferred embodiment of the invention, the carbon yield of the matrix material and / or the unsaturated compound during pyrolysis is ≥40%, preferably ≥50%, more preferably ≥55%, even more preferably ≥60%, and most preferably ≥65%. The carbon yield can be determined by thermogravimetric analysis, wherein about 30 mg of a sample is heat treated in an N2 atmosphere (purge gas rate of 60 ml / min) and a linear heating program from 20°C to 1000°C is run at a heating rate of 10°C / min. The carbon yield corresponds to the ratio of the residual mass of the matrix material or the unsaturated compound to the initial mass. The advantages according to the invention are particularly evident when the yield is correspondingly high.

[0072] The base material of the protective device according to the invention may also comprise additives.

[0073] Particularly preferably, the additive is a flame retardant, which is preferably selected from the group consisting of halogenated and / or nitrogen-based flame retardants, inorganic flame retardants (e.g., graphite salts, aluminum hydroxide, antimony trioxide, ammonium polyphosphate), aluminum diethylphosphinate, mica, muscovite, guanidine, triazine, sulfates, borates, cyanurates, their salts and mixtures thereof. The flame retardant activity of the protective device can thereby be further increased. Due to the inherent flame retardant activity caused by the carbonization behavior, significantly lower contents of additives (in particular flame retardants) can be used compared to the protective devices known from the prior art, which has a particularly positive effect on the mechanical properties of the protective device. In a preferred embodiment of the invention, the base material contains ≤50 wt % of additives, preferably ≤45 wt % of additives, more preferably ≤40 wt % of additives, further preferably ≤35 wt % of additives, even further preferably ≤30 wt % of additives, most preferably ≤25 wt % of additives, but also preferably ≥1 wt %.

[0074] In other preferred embodiments, the additives are selected from the group consisting of antioxidants, light stabilizers (especially UV stabilizers), plasticizers, foaming agents, electrical conductors, thermal conductors, dyes, fillers for improving mechanical properties (for example, impact modifiers, rubber or thermoplastic particles), and mixtures of the above substances.

[0075] The additive may be present in the matrix material in dissolved or dispersed form. If the additive is present in dispersed form, it is preferably contained in the form of a powder, tablet, tube or a mixture of the above forms.

[0076] If the additive is a flame retardant, it is preferably selected from the group of active (ie cooling) flame retardants, or from the group of passive (ie insulating) flame retardants. The flame retardant is particularly preferably an intumescent flame retardant.

[0077] Finally, the matrix material according to the invention may also contain a wetting agent. A wetting agent is a surface-active substance that generally has a hydrophobic molecule part and a hydrophilic molecule part. Wetting agents can be divided into nonionic, anionic and cationic types. The wetting agent reduces the viscosity of the resin. This improves the permeability of the fiber material, ultimately leading to a stronger bond between the fiber material and the matrix material. Therefore, the synergistic effect can be improved, in particular the stability of the (partially) carbonized structure can be improved.

[0078] For example, nonionic wetting agents are esters and amides of fatty acids (saturated or unsaturated carboxylic acids, which usually contain 4 to 26 carbon atoms in the molecule), fatty amines (primary amines, which usually contain 6 to 22 carbon atoms in the molecule), or polyethylene glycol ethers or polypropylene glycol ethers of alcohols, alkylphenols or fatty acid alkanolamides. For example, anionic wetting agents are salts of alkylmalonic or alkylsuccinic acids, alkyl sulfonates, fatty acid ester sulfonates, perfluoroalkyl sulfonates or sulfated fatty acid amides. Cationic wetting agents are substances such as salts of fatty amines, alkylenediamines and polyamines, alkylbenzylammonium salts or alkylpyridinium salts.

[0079] The fiber composite component (i.e. the protective device) is preferably of integral design, i.e. of one-piece design, i.e. of one-piece design. Particularly preferably, the fiber composite component is obtained during its production by one-piece curing. In a further preferred embodiment, the fiber composite component is a fiber composite sandwich panel, i.e. a plate-shaped component made in a sandwich structure.

[0080] The invention also relates to a protective device for a battery housing and / or a battery and / or a battery module as defined in any of the claims and the preceding and following sections of the description.

[0081] Particularly preferably, the protective device is a battery housing, in particular a battery housing for an electric vehicle battery, such as a lithium-ion battery.

[0082] Preferably, the protective device is a vehicle component, in particular a motor vehicle component, such as a body component. Particularly preferably, the protective device is an underbody protector (also known as a crash protection plate or underrun protection) or a bumper, or a battery housing, a battery housing part, and is preferably in the form of a protective plate.

[0083] The protective device may also be part of an aircraft or spacecraft, a rail vehicle component or a part of the above. More preferred motor vehicle components are selected from the group consisting of luggage compartment loading floors, dashboards, door linings and roof trims, underbody protection components, structural components, wheel housings, engine compartment components, brake and clutch linings and discs, sound insulation, thrust plates and seals.

[0084] The protective device is particularly preferably used as part of a battery housing, in particular for a lithium-ion battery (the battery housing is not necessarily part of the motor vehicle). The fiber composite material component is particularly preferably a floor panel or a cover panel.

[0085] The protection device may also be an "inter-cell barrier".

[0086] The invention also relates to a fiber-matrix semi-finished product, preferably a prepreg, for producing a protective device according to the invention, which fiber-matrix semi-finished product has a fiber material comprising or consisting of long fibers and / or continuous fibers, and a preferably curable, in particular heat-curable resin composition, which contains an unsaturated compound, which is preferably in the form of a resin having at least one structural repeating unit, wherein the fiber material is at least partially, preferably completely, embedded in the preferably heat-curable resin composition.

[0087] At least one structural repeating unit of the resin preferably used contains at least one functional group having an unsaturated carbon-carbon bond or an unsaturated carbon-nitrogen bond.

[0088] Preferably, the fiber-matrix semi-finished product is designed such that at least one surface of the semi-finished product is substantially completely (i.e. more than 70%), preferably completely, covered with matrix material. Such a fiber-matrix semi-finished product is characterized by particularly good processing properties. In particular, complex components can be produced by laminating other fiber layers with the completely covered side, thereby resulting in as small a interlayer pore volume as possible. The resulting protective device can therefore withstand particularly strong mechanical loads. The invention also relates to a protective device obtained by thermally bonding such a semi-finished product.

[0089] The preferably used curable resin composition of the fiber-matrix semi-finished product comprises or preferably is a phenolic resin, in particular a novolac resin, which is particularly preferably dry, i.e. has less than 10 wt. %, preferably less than 5 wt. %, even more preferably less than 1 wt. % of solvent. This dry, preferably heat-curable resin composition of the fiber-matrix semi-finished product is preferably obtained by partial curing with a curing agent, preferably an amine curing agent such as hexamethylenetetramine. The above-mentioned phenolic resins, in particular novolac resins, in particular the phenolic resins in the above-mentioned preferred embodiments, exhibit high storage stability and handling stability (in particular low or no tack) at room temperature, even at temperatures up to 60° C. This high stability is particularly evident when the phenolic resin, in particular the novolac resin, is in the "B stage", because further polymerization and crosslinking reactions do not occur at this time, or only occur to a lesser extent. This is particularly preferably achieved by partially curing the preferably heat-curable composition with an amine curing agent (for example hexamine). Preferably, the glass transition temperature (T g ) ≥ 4°C, preferably ≥ 8°C, more preferably ≥ 12°C, even more preferably ≥ 15°C, and most preferably ≥ 20°C. By using a linear phenolic resin, especially using a phenolic resin having the above T gThe high-quality novolac resin prevents the fiber-matrix semi-finished product from having a sticky feel. As a result, the fiber-matrix semi-finished product also has particularly good cuttability.

[0090] Preferably, the weight ratio of the fiber material in the fiber-matrix semi-finished product is in the range of 25-60wt%, preferably 30-55wt%, even more preferably 35-50wt%, most preferably 35-50wt%. Within these value ranges, both dry spots in the fiber-matrix semi-finished product and excessive matrix outflow in process control can be avoided.

[0091] By using novolac resins, coloration phenomena in the fiber-matrix semifinished product and / or the protective device, as occurs when using resol resins (Resol), can generally be avoided.

[0092] When phenolic resins (especially linear phenolic resins) are used as fiber-matrix semi-finished products, the heat-curable composition is preferably in the so-called "B stage", i.e. the composition is still swellable and meltable, but is no longer soluble in the solvent. This stage is usually achieved by heat treatment at a maximum temperature of 160° C. Such resins can be integrated particularly easily with surface films, treatment films, protective films (especially UV protective films), marking films and color films, as well as films for improving electromagnetic compatibility (EMC). Also particularly preferred are covering functional layers, such as protective films for transportation and in-mold coatings, for example, for improving paintability. Therefore, the fiber-matrix semi-finished product preferably includes such a film. The protective device according to the invention also preferably includes such a film. The use of phenolic resins, especially phenolic resins in the "B stage", also allows near-net-shape pressing (endkonturnahes Pressen) to be achieved due to their low fluidity.

[0093] In terms of process technology, the use of the above-mentioned phenolic resins (especially linear phenolic resins) in the "B stage" can further simplify the process because the reaction is highly completed before the final curing in the final component production process. This simplifies and speeds up the entire process. In the case of using linear phenolic resins and amine curing agents, in the final curing process of the fiber-matrix semi-finished product of the protective device according to the present invention, only ammonia is released, and the basic structure of the curable composition in the "B stage" is no longer changed. This leads to a high degree of application diversity (producing a "phenolic resin-based organic sheet"), and the reaction time in the final curing step is very short. In addition, ammonia is significantly easier to escape from the resin matrix, so compared with dehydration curing (for example, when curing with a hydroxymethyl-containing compound), the observed pore formation is significantly less. Therefore, a thicker and more stable protective device can be produced.

[0094] The invention also relates to a system ("kit of parts") for producing a fiber-matrix semi-finished product as defined in claim 14 and above, wherein the composition comprises a fiber material and a preferably heat-curable resin composition in powder form. The resin composition is preferably dry, i.e. has less than 10 wt. %, preferably less than 5 wt. %, even more preferably less than 1 wt. % of solvent. The dry, preferably heat-curable composition preferably contains a curing agent, in particular an amine, such as hexamethylenetetramine (also known as "hexamine"). In the powdered system, the preferably heat-curable composition is preferably in the "A stage", in particular in the "A2 stage".

[0095] In the process, additives can be easily added using a powder spreader. Additives can be added as separate powders. Preferably, additives (particularly curing agents) are added in a manner that is substantially uniformly distributed in the resin powder. Compared with using a separate powder of a heat-curable composition and a curing agent, in this way, powder separation caused by density differences during the manufacturing process can be avoided, and the uniform distribution of the curing agent in the fiber-matrix semi-finished product can be ensured. Therefore, the system also preferably includes a curing agent that is dissolved and / or dispersed in a powdery, heat-curable resin composition. In another embodiment, the system includes a curing agent as a separate powder. However, preferably, additives, particularly curing agents are dissolved and / or dispersed in the resin composition.

[0096] The present invention also relates to the use of the protective device according to the present invention in a battery structure. The present invention also relates to the use of the protective device according to the present invention for protecting batteries and / or battery housings, and / or for protecting batteries, more precisely, for preventing dangers caused by batteries. The present invention also relates to the use of unsaturated compounds in protective devices for battery housings and / or batteries and / or battery modules, in particular in protective devices for battery housings and / or batteries and / or battery modules for electric vehicles, the unsaturated compound being in particular a thermosetting polymer material having at least one structural repeating unit containing an unsaturated carbon-carbon bond and / or an unsaturated carbon-nitrogen bond. In particular, in protective devices for battery housings of electric vehicles, it is particularly preferred to use a thermosetting polymer material obtained by curing a phenolic resin, in particular a linear phenolic resin, as a matrix material for the protective device for the battery housing. The invention also relates to the use of a thermosetting polymer material obtained by crosslinking a phenolic resin, in particular a novolac resin, as a matrix material in a battery structure comprising a protective device for a battery housing and a battery housing and / or a battery and / or a battery module, wherein the protective device and / or the battery and / or the protective device and the battery housing and / or the protective device and the battery module are preferably connected to one another. Particularly preferably, the protective device is arranged on one of the inner or outer sides of the battery housing and / or the battery, in particular fastened thereto.

[0097] The invention also relates to the production of a fiber-matrix semi-finished product and a protective device made from the fiber-matrix semi-finished product.The method for producing a protective device comprises a first step for producing a fiber-matrix semi-finished product and a subsequent step for heat setting and is illustrated by the following example.

[0098] Step 1: Production of fiber-matrix semi-finished product by powder lamination

[0099] In the first step of producing the protective device, a novolac resin with a weight-average molecular weight of about 500 g / mol is applied to the textile, melted at a temperature of 120-130 ° C, and then a force (> 5 N / cm 2 ), thereby pressing it into the fiber material. By cooling, a fiber-matrix semi-finished product is obtained. The degree of conversion of the heat-curable matrix material (i.e., the degree of partial curing) can be adjusted by the pressing time and / or the pressing temperature and / or the pressing pressure. Thus, the brittleness of the material can be controlled. After cooling, the linear phenolic resin is in the "B state".

[0100] Step 2: Heat setting to produce the protector

[0101] In the subsequent second method step, the fiber-matrix semi-finished product obtained in step 1 is processed at a higher temperature by means of a shaping and heating tool (about 140-170° C.) into the desired final contour (e.g., L-profile, etc.). Preferably, a plurality of fiber-matrix semi-finished products can be stacked together, i.e., a so-called stack, in order to thereby obtain a homogeneous final product after final curing.

[0102] Step 1 and step 2 can be carried out either continuously (i.e., directly in succession in time) or discontinuously (i.e., separated in time). The method according to the invention makes it possible to produce components, such as laminates, which have significantly thicker walls than the components known from the prior art. Conventional casting resin systems are generally difficult to process due to the amount of resin, the impregnation distance and the exothermic properties, so that the component thickness is limited in this case. This is particularly true for conventional wet spraying processes, as the resin system can no longer fully penetrate the fiber layer above a certain thickness.

[0103] On the other hand, when using the RTM process, one or more gate points are used, which are usually not perfectly hidden from view. In addition, the gates always lead to an uneven distribution of the matrix material, since the fiber material can hardly penetrate completely due to the above-mentioned problems, especially in large structures.

[0104] Since, in the method according to the invention, the final component is obtained by joining thin layers which are almost completely impregnated with resin, these problems do not exist in this case.

[0105] Therefore, in a preferred embodiment of the present invention, the protective device according to the present invention is a protective plate with a thickness of ≥1 mm, preferably ≥1.5 mm, more preferably ≥2.5 mm, even more preferably ≥3.5 mm, and most preferably ≥5 mm. In such a protective plate, the fiber material is preferably substantially completely (i.e. more than 95 vol%) embedded. Preferably, the protective device is obtained by a method comprising the following steps:

[0106] I) Production of a fiber-matrix semi-finished product by:

[0107] a) applying a dry, powdered and heat-curable resin composition, in particular a novolac phenolic resin to produce phenoplasts, to the textile;

[0108] b) melting the resin composition at 100-150° C.; and

[0109] c) applying force to allow the resin to penetrate the textile,

[0110] II) producing a protective device from one or more fiber-matrix semi-finished products produced in step I) by:

[0111] a) optionally: stacking a plurality of fiber-matrix semi-finished products in a press;

[0112] b) Pressing the fiber-matrix semifinished product or a stack of the fiber-matrix semifinished products at a temperature of 150° C. to 250° C., in particular 160° C. to 180° C.

[0113] The method according to the invention also allows the use of materials with a low surface density (≤ 200 g / m 2 ) which cannot be processed in conventional manufacturing methods such as wet pressing due to the difficulty of penetration. Therefore, the present invention preferably relates to a fiber-matrix semi-finished product and a protective device, which comprises a fine fabric with an area density of ≤200 g / m 2 , preferably ≤150g / m 2 , even more preferably ≤120g / m 2 , and most preferably ≤90g / m 2 Preferably, the protective device with the corresponding fabric is obtained by a method comprising the steps defined above. BRIEF DESCRIPTION OF THE DRAWINGS

[0114] The present invention will be described in more detail below based on exemplary embodiments shown in the accompanying drawings.

[0115] Figure 1 and Figure 4 Step 1 of the method for producing a protective device according to the invention is schematically shown.

[0116] Figure 2 Step 2 of the method for producing a protective device according to the invention is schematically shown.

[0117] Figure 3 A multi-matrix protection device with locally different matrix systems is schematically shown. DETAILED DESCRIPTION

[0118] Figure 1 and Figure 4 A method for producing a protective device according to the invention, ie a composite component, which can be used, for example, for a cover or a bottom of a battery housing of an electric vehicle is shown schematically and by way of example.

[0119] To produce such composite parts, the unwinder is equipped with a glass fiber fabric. The total grammage of the glass fiber fabric and the distribution of the proportions of different fiber orientations (e.g. 0°, + and -45° and 90° relative to the longitudinal axis of the vehicle) are determined during the design process based on the mechanical and other loads on the cover / bottom. In a simple basic structure, the orientations of 0°, -45°, 45° and 90° are in equal proportions, so a so-called quasi-isotropic laminate is used.

[0120] With the help of an unwinder, the glass fiber fabric is fed into a powder lamination system with a powder spreader. With the help of a powder spreader, a resin-curing agent mixture in powder form is spread on the fabric surface and then fed into a double belt press (the press temperature is about 120°C). The resin material is a linear phenolic resin with a weight average molecular weight of about 500 g / mol, and the curing agent is hexamine. Thus, the resin material is pressed into the fabric, and thus the reinforcing fibers are embedded in the resin. Figure 1 and Figure 4 The process steps are schematically shown. After cooling to room temperature, the obtained prepreg is cut and / or rolled or stacked. The fiber-matrix semi-finished product (prepreg in this case) thus obtained is storage-stable at room temperature (about 23° C.) (i.e., does not convert to the "C-stage" for at least 2 days) and is substantially non-sticky.

[0121] To produce the protective device, the semi-finished product is cut to shape in step 2 of the method and then stacked to the desired thickness. The stack is then placed in an open press with a pressing edge, the press is closed, and the component is pressed in a path-controlled manner at a temperature of 160-170°C to completely cure the matrix material. The curing time is several minutes. Figure 2 The process steps are shown schematically.

[0122] The part is then removed from the mold and sent to final processing steps.

[0123] Depending on the arrangement of the battery cells in the housing, certain areas of the cover are exposed to particularly high temperatures in the event of a battery fire. Therefore, in one embodiment of the invention, the base material of the protective device contains an unsaturated base material, such as a novolac resin, only at these locations exposed to particularly high loads. Figure 3 These locations are highlighted in black in the schematic diagram.

[0124] Reference numerals list

[0125] 1. Curable resin composition in powder form

[0126] 2 layers of textile fiber material

[0127] 3. Fully resin-coated surface side of the fiber-matrix semi-finished product

[0128] 4Fiber-matrix semi-finished products

[0129] 5. Protective device

[0130] 6. Novolac-enriched matrix area of ​​the protection device

[0131] 7 Unwinding machine with glass fiber fabric

[0132] 8 Powder Spreader

[0133] 9 Heating zones of double belt press

[0134] 10Cooling zone of double belt press

[0135] 11Semi-finished product winding device

Claims

1. A battery structure comprising a battery housing and / or a battery and a protective device, wherein: The protection device comprises: a) fibrous materials comprising long fibers and / or continuous fibers; and b) Matrix material, wherein the fiber material is at least partially, preferably completely, embedded in the matrix material, It is characterized in that The matrix material comprises an unsaturated compound, preferably an unsaturated polymer, or consists of such a material.

2. The battery structure according to claim 1, wherein: The protective device at least partially, preferably completely, consists of a fiber material, preferably in the form of a textile surface structure.

3. The battery structure according to claim 2, wherein: The textile surface structure is selected from the group consisting of laid scrims, woven fabrics, nonwoven fabrics or combinations thereof.

4. A battery structure according to any one of the preceding claims, wherein: The fibers of the fiber material are selected from the group consisting of glass fibers, carbon fibers, basalt fibers, ceramic fibers, steel fibers, polymer fibers, such as synthetic fibers, in particular aramid fibers and nylon fibers, or natural polymer fibers, such as flax fibers, hemp fibers or protein fibers.

5. A battery structure according to any one of the preceding claims, wherein: The unsaturated compound is a thermosetting polymer material having at least one structural repeating unit with at least one functional group containing an unsaturated carbon-carbon bond and / or an unsaturated carbon-nitrogen bond.

6. The battery structure according to claim 5, wherein: The functional group contains an unsaturated carbon-carbon double bond.

7. The battery structure according to claim 5 or 6, wherein: The functional group includes two or more bonds selected from the group consisting of an unsaturated carbon-carbon bond and an unsaturated carbon-nitrogen bond, and wherein at least two of the bonds are conjugated.

8. The battery structure according to any one of claims 5 to 7, wherein: The at least one functional group is selected from the group consisting of a carbon-carbon double bond, a carbon-carbon triple bond, an imino group, an aromatic group and a nitrile group, and / or the at least one functional group is part of one of the following residues: an alkenyl group, an alkynyl group, a nitrile group, a furanyl group, a thienyl group, a pyrrolyl group, an imidazolyl group, a pyrazolyl group, an oxazolyl group, a thiazolyl group, a phenyl group, a benzoyl group, a hydroxyphenyl group or a pyridyl group.

9. A battery structure according to any one of the preceding claims, wherein: The protection device is of one-piece design or has a sandwich structure.

10. A battery structure according to any one of the preceding claims, wherein: The unsaturated compound is a thermosetting polymer produced by curing a curable resin composition, wherein the resin of the resin composition is preferably selected from the group consisting of phenolic resins, melamine resins, polyurethane resins and mixtures thereof, and the phenolic resin is particularly a linear phenolic resin.

11. A battery structure according to any one of the preceding claims, wherein: The battery structure comprises a battery housing, and the protection device is the battery housing or a part of the battery housing, preferably a bottom plate or a cover plate.

12. Protective device for a battery housing and / or a battery and / or a battery module as defined in any one of the preceding claims.

13. A protection device according to any one of the preceding claims, wherein: The protective device is a vehicle component, preferably a motor vehicle component or a part of the motor vehicle component, the motor vehicle component is preferably a part of a battery housing, particularly preferably a floor panel or a cover panel.

14. A fiber-matrix semi-finished product for producing a protective device according to any one of the preceding claims, comprising: a) fibrous materials comprising long fibers and / or continuous fibers; as well as b) a curable resin composition comprising an unsaturated compound, Therein, the fiber material is at least partially, preferably completely, embedded in the curable resin composition.

15. Use of unsaturated compounds in protective devices for battery housings and / or batteries, in particular in protective devices for battery housings of electric vehicles, wherein the unsaturated compounds are in particular thermosetting polymer materials having at least one structural repeating unit containing unsaturated carbon-carbon bonds and / or unsaturated carbon-nitrogen bonds.

Citation Information

Patent Citations

  • Fire shielding battery case

    US20050170238A1

  • Electric vehicle battery pack cover having composite structure

    US20200152926A1